No effect of patent foramen ovale on acute mountain sickness and pulmonary pressure in normobaric hypoxia. Issue 2 (10th January 2022) - DiMarco, Kaitlyn G.; Beasley, Kara M.; Shah, Karina; Speros, Julia P.; Elliott, Jonathan E.; Laurie, Steven S.; Duke, Joseph W.; Goodman, Randall D.; Futral, Joel Eben; Hawn, Jerold A.; Roach, Robert C.; Lovering, Andrew T.
Abstract : New Findings: What is the central question to this study? Is there a relationship between a patent foramen ovale and the development of acute mountain sickness and an exaggerated increase in pulmonary pressure in response to 7–10 h of normobaric hypoxia? What is the main finding and its importance? Patent foramen ovale presence did not increase susceptibility to acute mountain sickness or result in an exaggerated increase in pulmonary artery systolic pressure with normobaric hypoxia. This suggests hypobaric hypoxia is integral to the increased susceptibility to acute mountain sickness previously reported in those with patent foramen ovale, and patent foramen ovale presence alone does not contribute to the hypoxic pulmonary pressor response. Abstract: Acute mountain sickness (AMS) develops following rapid ascent to altitude, but its exact causes remain unknown. A patent foramen ovale (PFO) is a right‐to‐left intracardiac shunt present in ∼30% of the population that has been shown to increase AMS susceptibility with high altitude hypoxia. Additionally, high altitude pulmonary oedema (HAPE) is a severe type of altitude illness characterized by an exaggerated pulmonary pressure response, and there is a greater prevalence of PFO in those with a history of HAPE. However, whether hypoxia per se is causing the increased incidence of AMS in those with a PFO and whether a PFO is associated with an exaggerated increase in pulmonary pressure in those without a history of HAPE is unknown. Participants ( n = 36) matched for biological sex (18 female) and the presence or absence of a PFO (18 PFO+) were exposed to 7–10 h of normobaric hypoxia equivalent to 4755 m. Presence and severity of AMS was determined using the Lake Louise AMS scoring system. Pulmonary artery systolic pressure, cardiac output and total pulmonary resistance were measured using ultrasound. We found no significant association of PFO with incidence or severity of AMS and no association of PFO with arterial oxygen saturation. Additionally, there was no effect of a PFO on pulmonary pressure, cardiac output or total pulmonary resistance. These data suggest that hypobaric hypoxia is necessary for those with a PFO to have increased incidence of AMS and that presence of PFO is not associated with an exaggerated pulmonary pressor response.